The PI3K Pathway: Background and Treatment Approaches - Lux, Michael P.; Fasching, Peter; Schrauder, Michael G.; Hein, Alexander; Jud, Sebastian; Rauh, Claudia; Beckmann, Matthias (Breast Care, 2016)
Two-thirds of all breast cancer patients with metastases have a hormone receptor (HR)-positive/human epidermal growth factor receptor 2 (HER2)-negative subtype. Endocrine therapy is the treatment of choice in these patients since in addition to its effectiveness it can also maintain the patients' quality of life over a longer term. However, 44-62% of postmenopausal patients with metastatic breast carcinoma have primary tamoxifen resistance. After 3-5 years, 30-40% of the patients receiving tamoxifen treatment develop secondary resistance. Understanding the way in which resistance develops is therefore essential for developing treatment approaches that can prevent or reverse endocrine resistance. The phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling pathway plays a central role here. As a result of the numerous interactions involved, complex issues arise that need to be taken into account in the development and use of therapeutic agents. In addition, this signaling pathway is the one that most frequently undergoes mutations in breast cancer. The prognostic and predictive significance of individual mutations has not yet been fully explained, but it might provide a basis for patient selection in clinical studies. Initial research results on the use of PI3K inhibitors suggest that this may be a highly promising therapeutic approach, with an acceptable side effect profile.
EVALuna2:33003